PERKEMBANGAN EMBRIO DAN PERFORMA AWAL LARVA IKAN TAWES (Barbonymus gonionotus) - Wahyulia Cahyanti; Fia Sri Mumpuni; Salman Hijran Maulidie; Otong Z Arifin (Universitas Djuanda, 2022)
The research was carried out from November 2021 to January 2022, and the trial period from November 1 to November 12, 2021 at the Germplasm Research Installation for Freshwater Fisheries in Cijeruk, Bogor, West Java. This study aims to determine the embryonic development and early performance of Tawes fish (Barbonymus gonionotus) larvae. This experimental study used 2 male tawes broodstock, 2 female brood fish, and anesthetic drugs. Parameters observed included observation of embryos and early performance of Tawes larvae. The embryo data were analyzed in a qualitative descriptive manner with pictures of each phase of egg development and followed by data on egg hatching time. The results showed that the early embryonic development of Tawes fish generally includes the stages of egg division, morula, blastula, gastrula, segmentation and hatching. The initial performance of Tawes larvae reared at 28oC showed abnormality values ​​of Tawes fish of 5.78±1.52%, average egg diameter of 1.02±0.04 mm, average initial length of larvae of 7.28±0.55 mm.